Superoxide-mediated regioselective deblocking of the tosyl group from N-tosylcarboxamides - Raghuvanshi R.S.; Singh K.N. (My University, 2025)
In situ-generated tetraethylammonium superoxide brings about an easy and selective cleavage of the N-S bond of N-tosylcarboxamides, providing a new method for the deblocking of the tosyl group from such substrates. Copyright © Taylor & Francis Group, LLC.